Electronic structure and magnetic excitations of magnetic superconductors - Cantarino, Marli dos Reis (2023)
The manipulation of electron counting and orbital occupation via chemical doping, chemical pressure, hydrostatic pressure, or strain can tune the ground state of a material. Iron-based superconductors (FeSC) is a class of materials in which high-temperature superconductivity (SC) can emerge using these strategies. This transition occurs in the presence of strong magnetic fluctuations, suggesting a low sensitivity to magnetic impurities. Surprisingly, when it comes to transition metal substitution, electron dopants can cause SC to emerge, while hole dopants do not. This study employs Angle-Resolved Photoemission Spectroscopy (ARPES) to investigate the effect of hole doping in the Fe site of Ba(Fe1-xMx)2As2 (M = Mn, Cr) samples, probing the electronic band structure and its dependency on composition and temperature. The presented results show that for the case of Mn-substituted samples (MnBFA), electron and hole pockets remain nested, with Mn introduction mainly increasing the incoherence of the electronic bands and electronic correlations. These findings suggest that Mn tunes the material to a region between the correlated metal phase in BaFe2As2 and the Mott insulating phase in BaMn2As2, where disordered electronic phases can emerge. In the case of Cr substituted samples (CrBFA), hole doping was shown to take place, detuning the nesting condition between hole and electron states, and the electronic correlations increase with Cr content. However, no evidence of Mott phase behavior is observed in the ARPES experiments of the Cr-doped sample near the half-filling condition. Moreover, Resonant Inelastic x-ray Scattering (RIXS) was applied to probe the Fe-derived magnetic excitations in these materials. The RIXS experiments of CrBFA suggest a scenario that is slightly different from that for MnBFA samples but also shows strong magnetic scattering between Fe and Cr-derived excitations. This study explains the absence of SC in MnBFA as a combination of magnetic pair-breaking, disorder, and electronic correlations, while in CrBFA this absence is understood to be caused mainly because of magnetic pair-breaking and suppression of the itinerant spin fluctuations which promote the SC. These results shed light on the complex interplay between doping, magnetism, and electronic correlations in FeSC and correlated electron systems in general.